Maternal buffering of stress response in free‐ranging Pacific harbor seal pups in Alaska. Issue 3 (13th April 2015) - Di Poi, Carole; Atkinson, Shannon; Hoover‐Miller, Anne; Blundell, Gail
Abstract We examined the effects of maternal buffering in free‐ranging Pacific harbor seal pups during capture and handling research procedures. We predicted that pups held with their mother would benefit from social buffering and exhibit lower cortisol concentrations resulting from capture and handling than dependent pups caught without their mothers and weaned pups. We expected that pups captured with their mother that experienced a short separation would exhibit increased stress‐induced vocal behavior and activity level compared to dependent weaned pups caught alone. The results showed that the presence of the mother significantly buffered the stress response, as measured by reduced serum cortisol concentrations, in pups captured with their mothers as compared to dependent pups captured alone. Cortisol concentrations of mothers with pups initially were higher than nonlactating females, then diminished. Pups showed a significantly higher rate of vocalization soon after maternal separation compared to single pups separated for a longer period of time. Newly separated pups, especially males, showed a high level of activity compared to the other pups. The results provide unique quantitative evidence of the physiology underlying the maternal‐pup bond in a marine mammal, and the role that maternal buffering may play on the stress response of the offspring.